Kain Tenun “ Kamooru “ Di Kabupaten Muna (1990 – 2019) - Ana Fajarningsi; Andi Ima Kesuma; Ahmadin Ahmadin (Phinisi Integration Review, 2020)
The study discusses on woven fabric typical of Muna district, which is one of the distinctive cultural heritages of Muna ethnic. The weaving craft is done by weavers by using gedogan tools and ATBM. The Masalili village is the center of a weaver village in Muna district, which has a unique weaving and is rich in decorative motifs. The focus of this study is the history of making Muna woven fabric so it shows its existence to date as well as explain and document various kinds of woven motifs that are produced so it shows its development without eliminating traditional elements. Based on this topic, the purpose of this study is to determine the initial process of making Muna weaving in Masalili village, Kontunaga sub-district in Muna district to produce a variety of motifs and philosophies existed on the fabric sheet. This research method employed descriptive analysis with a qualitative approach. Data collections were conducted with literature study, observation, interview, and documentation. In this study, the author tries to explain brief history of the originator of Muna weaving, the process of making Muna weaving using gedogan tools and ATBM, the marketing flow of Muna weaving, and the existence of Muna weaving so it can marketed internationally.